(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
The interaction of chromium(VI) with 2-(3-(azepan-1-yl)-2-hydroxypropilthio) acetic acid has been studied by means of potentiometric, amperometric and spectrophotometric titration methods. The titration is possible to carry out in the acidity range 3.0-7.0 mol / L by sulfuric acid. Molar ratio of the reacting agents is [Cr(VI)] : [Reagent] = 2 : 3. Conformity to the Beer’s law is preserved when 8.3·10^6-2.0·10^3 mol / L at E=+0.2 V and when 2.0·10^5-2.0·10^3 mol / L at E =+1.2 V chromium(VI) solutions were titrated. The technique elaborated has been approved during the analysis of standard chromium-containing ore with standard relative deviation 0.61% . Possible scheme describing the interaction of chromium(VI) with the reagent has been suggested.